ESKATOLOGI ISLAM SHIA: ESKATOLOGI DUA DIMENSI | SHIA ISLAMIC ESCHATOLOGY: A TWO DIMENSIONAL ESCHATOLOGY - Justin L Wejak (Institut Filsafat dan Teknologi Kreatif Ledalero, 2018)
Abstract This paper explains an Islamic eschatology according to Shia, and suggests that []Shia eschatology always has two dimensions – religion and politics – and the two dimensions are inseperable. Discussion surrounding Shia eschatology in this paper is particularly focused on the Mahdism concept and the figure of Mahdi. This paper is thus not intended to make a generalisation about ‘Islamic eschatology’ as if there were only one type of Islam with a single understanding of eschatology. Most Indonesian Muslims are of Sunni type of Islam, and may not share the viewpoint of Shia at all concerning eschatology. The key purpose of this paper is rather to explore one version of understanding of eschatology within Islam in order to provoke further reflection on other perspectives on eschatology. Keywords: Eschatology, Islam, Politics, Religion, Shia, Sunni, Prophet Muhammad, Mahdism, Mahdi Abstrak Tulisan ini menjelaskan sebuah eskatologi Islam menurut Shia, dan mengusulkan bahwa versi eskatologi Shia selalu memiliki dua dimensi – agama dan politik – dan keduanya tak terpisahkan. Pembahasan mengenai eskatologi Shia dalam tulisan ini khususnya berfokus pada konsep Mahdisme dan figur Mahdi, menurut versi Islam Shia. Maka tulisan ini tak dimaksudkan untuk membuat generalisasi mengenai ‘eskatologi Islam’ seolah ada hanya satu jenis Islam dengan pemahaman tunggal mengenai eskatologi. Kebanyakan kaum Muslim Indonesian adalah penganut Sunni, dan barangkali samasekali tak sependapat dengan pandangan Shia tentang eskatologi. Tujuan utama tulisan ini sebetulnya untuk menjelaskan satu versi pemahaman eskatologi dalam Islam agar memprovokasi refleksi lebih lanjut tentang perspektif-perspektif lain terkait eskatologi. Kata-Kata Kunci: Eskatologi, Islam, Politik, Agama, Shia, Sunni, Nabi Muhammad, Mahdisme, Mahdi.